Dr. Hugh McLean — Deep Plane Facelift — Mississauga - McLean, Hugh (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Hugh McLean, practicing in Mississauga, Canada. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003167; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; canada; mississauga